Following the Pied Piper. Framing of the Catalan independence movement in 2014 and 2015 votings - A. Ballesteros Herencia, Carlos (Estudios sobre el Mensaje Periodístico, 2017)
The debate about the independence of Catalonia became the main theme of the Catalonian regional elections of 27 September 2015. A year earlier, on November 9, 2014, there had been a controversial referendum on the same subject. In this research the informative representations of both electoral calls made by major newspapers of Madrid and Catalonia were contrasted. A quantitative content analysis was conducted to calculate descriptive and inferential statistics, which showed the utmost importance given to this issue during the period of the election campaign. Besides the emergence of new sources, such as economic and international actors, were detected. The antagonistic news framing among the Catalonian and Madrid newspapers remained.
Keywords: Political news; news frames; framing; Cataluña.